Cross sectional determinants of IPO underpricing in China. - Toh, Daniel Ming Yuan. (2011)
Using a dataset of 859 Initial Public Offerings (IPOs) for the period of 1995 to 2011, we empirically examine the determinants of IPO underpricing in China. We document that the amount of capital raised, the proportion of major ownership, and P/E ratio are negatively associated with the level of underpricing of IPO. In addition, the age of a company, the listing time lag, and the oversubscription rate of the IPO are found to be positively related to IPO underpricing. Our multiple regression analysis indicates that the abovementioned determinants collectively account for roughly 37% of the variation in the level of underpricing across firms going public. Furthermore, we document that IPO underpricing in China is lower in more recent years and lower in Shanghai Stock Exchange (SHSE) as opposed to Shenzhen Stock Exchange (SZSE).